INTEGRASI AGAMA DAN SAINS DALAM PERSFEKTIF TASAWUF DAN KEBUDAYAAN - Rendra Khaldun (Universitas Islam Negeri (UIN) Mataram, 2015)
Mysticism and culture integration in its relation will show the same hing because culture is reality which has been created, produced, formed, and institutionalized. While in social context, culture is human product which is running continually. Cultureis formed by a group which is done continually and admitted by society. So in reality religion is always identical with tradition becauseculture is expression which is believed by people toward holy thing. If the connection between religion and tradition are placed as interpretational form of history and culture, all religious domains are human creativities which are characteristically relative. It means that religious truth which is believed by each person is as something “true”. Basically, it can only be interpreted and expressed by relative humanfor “the truth”, God is an absolute one. Then anything is done by human to defend, renew, and purify religious tradition; it should be seen as human phenomena for history without saying that the one is the truest one.